The Age as a Precondition of Criminal Responsibility - Margaryan, A. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The person can be held responsible for an offence committed if he/she has reached the minimum age of criminal liability. The age of criminal responsibility varies through 53 states having 6 as a minimum and going up to 18. RA legislation sets 16 as a general and 14 as an exceptional minimum age of criminal responsibility. However such a dualistic approach creates problems when trying to justify for which crimes the age of criminal responsibility should be set to 16 and for which – to 14. The author tries to respond to this and other issues concerning the age of criminal responsibility. As a conclusion, the author suggests to set a unified age of criminal responsibility for the committal of all types of crime.
Keywords: age, criminal responsibility, crime, child, criminal legislation, Beijing rules, Child rights